Ibn Jemaah's Directives for Verbal Similarities in Surat Yassin and As-Safat - Ismail , Saja Walid (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to explain the previous sayings, the validity of what the violators went in guiding them in that what is meant by the bright summer and winter and their Maghreb because the verses came to show the power of ALLAH and the greatness of his creation, and in this Ibn Ashour (may ALLAH have mercy on him) says: (And praise the Easters and the Moroccans as the sun rises In the winter and spring seasons of Samt, and in the summer and autumn seasons of another azimuth, taking into account the time of height and the time of the palace, as well as its sunset, and it is between these east and west, its rise and sunset are transmitted in similar degrees, so it may be considered that it is said: the east and west, as in the Almighty says:And whoever claims that the praise of the Easters to observe the sun and moonshining, as well as the Deuteronomy of the Maghrib, does not dictate much meaning, and the interpretation of the public by the East (and) the Moroccans (the East and the West, the meaning of (the East) is the eastern half of the land, and (the Moroccans) the western half of it, And the ALLAH head of ALLAH Almighty for the East and West in the sense of creation and behavior, and when the East and West indicated the views of lights, day and night, it is appropriate for the indication here to be on summer and winter, and as the rule says (the increase in the building indicates the increase in meaning and the strength of the word for the strength of the meaning), then the increase came To indicate all these meanings, and ALLAH knows best.